The structure of a strategic innovation project for a transport enterprise and the content of its modules - Vydrya, E. V.; Kobielieva, T. O.; Pererva, P. G. (ТОВ "Юридична компанія "Юрсервіс", 2023)
It has been proven that for employees of the logistics department, the appearance of the computerized rolling stock management system was an important element that facilitated the performance of tasks. However, there is no doubt that without the agreement of the top management, their understanding of the need to implement this innovative project, and above all its financing, it would be impossible to implement it.
Keywords: strategy; innovative project; structure; transport enterprise; effect